Varnish and cured product thereof
By using a varnish composed of polymer compounds and liquid monomers, combined with multifunctional monomers and olefin-aromatic vinyl compounds-aromatic polyene copolymers, the existing technology solves the problem of high viscosity, solvent drying and hardness of varnishes in the prior art. The problem of room for improvement in composition has led to improvements in low dielectric properties, low viscosity and high-temperature elastic modulus.
Patent Information
- Application Number
- CN202380046249.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-06
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, the varnish of the olefin-aromatic vinyl compound-aromatic polyene copolymer has a high viscosity, a solvent drying process is required, and a room for improvement in improving low dielectric properties, and an elastic mode at high temperature. Insufficient quantity and crosslink density.
The varnish uses polymer compounds and liquid monomer components, contains multi-functional monomers, has a number average molecular weight between 500 and 12,000, and does not contain solvents. The content of olefin-aromatic vinyl compound-aromatic polyene copolymer is within Between 30-69 mass%.
Realize the process of low mediators, low viscosity, and omitting solvent drying process, improve the elastic modulus and cross -linking density at high temperature, and apply to high -frequency insulation materials.
Smart Images

Figure BDA0005180343660000261 
Figure BDA0005180343660000262 
Figure BDA0005180343660000271
Abstract
Description
Technical Field
[0001] The present invention relates to a varnish containing a copolymer and a liquid monomer component, and an insulating material as a cured product thereof. Background Art
[0002] As communication frequencies develop toward the gigahertz band, and especially the millimeter wave band above 30 GHz, the low dielectric properties required of the insulator used in the multilayer substrate formed by CCL and FCCL have become more stringent. Fluorine-based resins such as perfluoroethylene have excellent low dielectric constant, low dielectric loss and excellent heat resistance, but are difficult to form and process, and film formability. In addition, there are also problems in terms of adhesion to the copper foil of the wiring, so it is difficult to apply to multilayer substrates. On the other hand, substrates and insulating materials using post-curing resins such as epoxy resins, unsaturated polyester resins, polyimide resins, and phenolic resins are widely used because of their heat resistance and ease of operation, but the dielectric constant and dielectric loss are relatively high, and as insulating materials for high frequencies, they are expected to be improved (Patent Document 1).
[0003] Therefore, hydrocarbon resins with low dielectric properties in nature have attracted much attention. Originally, in order to make hydrocarbon resins as thermoplastic resins into curable resins, it is necessary to introduce functional groups, but generally speaking, functional groups that react with free radicals or perform thermal reactions have polarity, so low dielectric properties will deteriorate. When it is desired to introduce functional groups consisting only of hydrocarbons, such as aromatic vinyl, there are many cases of using intermolecular reactions between expensive hydrocarbon monomers (patent document 2), which is not economical in many cases. Patent document 3 shows a solidified body, which is obtained by a specific coordination polymerization catalyst and includes ethylene-olefin (aromatic vinyl compound)-aromatic polyene copolymers and non-polar vinyl compound copolymers with specific composition and coordination. In the case of the technology disclosed in patent document 3, only one of the two vinyl groups of aromatic polyene (divinylbenzene) is selectively copolymerized and the remaining vinyl group is preserved, so it is easy to obtain a cross-linked hydrocarbon copolymer macromonomer with a functional group of aromatic vinyl. The solidified body obtained by the composition of the same olefin-aromatic vinyl compound-aromatic polyene copolymer and auxiliary raw materials etc. has the characteristics of low dielectric constant, low dielectric loss tangent (patent documentation 4,5). The varnish comprising the lower viscosity of the olefin-aromatic vinyl compound-aromatic polyene copolymer with lower molecular weight and the added resin, monomer and solvent is also known (patent documentation 6). The liquid curable resin composition comprising olefin-aromatic vinyl compound-aromatic polyene copolymer and non-polar vinyl compound is also known (patent documentation 7).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 6-192392
[0007] Patent Document 2: Japanese Patent Application Publication No. 2004-087639
[0008] Patent Document 3: Japanese Patent Application Publication No. 2007-217706
[0009] Patent Document 4: International Publication No. 2021 / 112087
[0010] Patent Document 5: International Publication No. 2021 / 112088
[0011] Patent Document 6: International Publication No. 2022 / 014599
[0012] Patent Document 7: Japanese Patent Application Publication No. 2009-161743 Summary of the invention
[0013] Problems to be solved by the invention
[0014] The olefin-aromatic vinyl compound-aromatic polyene copolymer of record in the above-mentioned open patent document, the cured product obtained by the composition comprising it all present good low dielectric properties, for example low dielectric loss tangent value.But the varnish shown comprises solvent, therefore needs to be used for removing the drying process (patent documentation 4,5,6) of solvent.In addition, the olefin-aromatic vinyl compound-aromatic polyene copolymer itself that the composition of record in these patent documentations 4,5,6 is used is soft, therefore comprises a large amount of hard components (for example, polyphenylene ether, bismaleimide etc.) with curable functional group.But these hard components have room for improvement in improving low dielectric properties.In addition, in order to further improve the elastic modulus when high temperature, need to increase the usage amount of these hard components, not yet obtain reducing hard components or even adding hard components also can maintain the view of excellent low dielectric properties. In addition, Patent Document 7 describes a solvent-free varnish, but the molecular weight of the copolymer used is high, so the viscosity of the varnish is high, and there is room for further improvement in the impregnation of glass cloth, etc. in applications such as CCL. In addition, in the formulations exemplified in Patent Document 7, the crosslinking density is low, and there is room for improvement in the elastic modulus at high temperature, for example.
[0015] Means for solving problems
[0016] The present invention can provide the following aspects to solve the problems that cannot be solved by the above-mentioned conventional techniques.
[0017] Method 1.
[0018] A varnish, characterized in that it comprises:
[0019] A polymer compound having a plurality of free radical reactive functional groups in the molecule and having a number average molecular weight (Mn) of 500 to 12,000; and
[0020] A monomer component having a free radical reactive functional group in the molecule, having a molecular weight of 300 or less and being liquid at room temperature,
[0021] The monomer component contains a multifunctional monomer, and the content of the multifunctional monomer is 31 mass % or more and 70 mass % or less of the total mass of the varnish, and
[0022] The varnish contains substantially no solvent component.
[0023] Method 2.
[0024] The varnish according to Embodiment 1, wherein the polymer compound is an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying all of the following conditions (1) to (4),
[0025] (1) the number average molecular weight of the copolymer is 500 or more and 12,000 or less,
[0026] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0 to 98% by mass.
[0027] (3) the aromatic polyene is one or more selected from polyenes having a plurality of vinyl and / or vinylidene groups in the molecule and having a carbon number of 5 to 20, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 2 to 30 in terms of number average molecular weight,
[0028] (4) It may contain one or more selected from olefin monomer units having 2 to 20 carbon atoms, and when aromatic vinyl compound monomer units and aromatic polyene monomer units are present, the total of the olefin monomer units and the aromatic polyene monomer units is 100% by mass.
[0029] Method 3.
[0030] The varnish according to Embodiment 2, wherein the content of the olefin-aromatic vinyl compound-aromatic polyene copolymer is in the range of 30% by mass or more and 69% by mass or less based on the total mass of the varnish.
[0031] Method 4.
[0032] The varnish according to any one of Embodiments 1 to 3, wherein the polyfunctional monomer contains divinylbenzene.
[0033] Method 5.
[0034] The varnish according to Embodiment 4, wherein the content of divinylbenzene is 30% by mass or more based on the total mass of the varnish.
[0035] Method 6.
[0036] The varnish according to any one of aspects 1 to 5, wherein the monomer component further contains a monofunctional monomer.
[0037] Method 7.
[0038] The varnish according to Embodiment 6, wherein the content of the monofunctional monomer is 40% by mass or less based on the total mass of the varnish.
[0039] Method 8.
[0040] The varnish according to embodiment 6 or 7, wherein the monofunctional monomer comprises one or more selected from styrene, ethylvinylbenzene or acenaphthylene.
[0041] Method 9.
[0042] A cured product of the varnish according to any one of aspects 1 to 8.
[0043] Method 10.
[0044] The cured product according to Embodiment 9, which is an electrically insulating material.
[0045] Method 11.
[0046] A CCL substrate, a FCCL substrate, an interlayer insulating material or a covering layer, comprising the cured body described in method 9 or 10.
[0047] Method 12.
[0048] A cross-linked resin matrix, characterized in that the cross-linked resin matrix is a cured product of a varnish containing an olefin-aromatic vinyl compound-aromatic polyene copolymer and a multifunctional monomer component,
[0049] The storage modulus of the cross-linked resin matrix at 280° C. is 30 MPa or more.
[0050] Method 13.
[0051] The cross-linked resin matrix according to Embodiment 12, wherein the storage modulus of the cross-linked resin matrix at 25° C. is 80 MPa or more.
[0052] Method 14.
[0053] The crosslinked resin matrix according to embodiment 12 or 13 has an average dielectric constant of 2.5 or less and 2.0 or more measured at 23° C. and 20 to 42 GHz using a balanced disk resonator, and an average dielectric loss tangent of 0.0012 or less and 0.0003 or more.
[0054] Method 15.
[0055] The crosslinked resin matrix according to any one of aspects 12 to 14, comprising 99 mass % or more of carbon and hydrogen.
[0056] Method 16.
[0057] The cross-linked resin matrix according to any one of aspects 12 to 15, wherein the varnish contains substantially no solvent component.
[0058] Method 17.
[0059] The cross-linked resin matrix according to any one of Embodiments 12 to 15, wherein the varnish contains a solvent component.
[0060] Method 18.
[0061] The crosslinked resin matrix according to any one of Embodiments 12 to 17, wherein the olefin-aromatic vinyl compound-aromatic polyene copolymer satisfies all of the following conditions (1) to (4),
[0062] (1) the number average molecular weight of the copolymer is 500 to 12,000,
[0063] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0 to 98% by mass.
[0064] (3) the aromatic polyene is one or more selected from polyenes having a plurality of vinyl and / or vinylidene groups in the molecule and having a carbon number of 5 to 20, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 2 to 30 in terms of number average molecular weight,
[0065] (4) It may contain one or more selected from olefin monomer units having 2 to 20 carbon atoms, and when aromatic vinyl compound monomer units and aromatic polyene monomer units are present, the total of the olefin monomer units and the aromatic polyene monomer units is 100% by mass.
[0066] Method 19.
[0067] A method for manufacturing a solidified body, the aforementioned manufacturing method comprising:
[0068] a step of preparing a varnish containing an olefin-aromatic vinyl compound-aromatic polyene copolymer and a multifunctional monomer component; and
[0069] A step of obtaining a cured product having a storage elastic modulus of 30 MPa or more at 280° C. by curing the varnish.
[0070] Method 20.
[0071] The production method according to Embodiment 19, wherein the storage modulus of the cured product at 25° C. is 80 MPa or more.
[0072] Method 21.
[0073] The production method according to embodiment 19 or 20, wherein the olefin-aromatic vinyl compound-aromatic polyene copolymer satisfies all of the following conditions (1) to (4),
[0074] (1) the number average molecular weight of the copolymer is 500 or more and 12,000 or less,
[0075] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0 to 98% by mass.
[0076] (3) the aromatic polyene is one or more selected from polyenes having a plurality of vinyl and / or vinylidene groups in the molecule and having a carbon number of 5 to 20, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 2 to 30 in terms of number average molecular weight,
[0077] (4) It may contain one or more selected from olefin monomer units having 2 to 20 carbon atoms, and when aromatic vinyl compound monomer units and aromatic polyene monomer units are present, the total of the olefin monomer units and the aromatic polyene monomer units is 100% by mass.
[0078] Effects of the Invention
[0079] According to the present invention, a cured product having excellent low dielectric properties, high elastic modulus and high crosslink density at room temperature and high temperature can be provided. This cured product is particularly useful as an insulating component of a rigid substrate. The varnish of the present invention can omit the process of drying the solvent, has low viscosity, and is highly adaptable to processes including impregnation. The obtained cured product can exhibit low dielectric loss tangent value and high high temperature elastic modulus, and is therefore particularly useful as a high-frequency insulating substrate material. DETAILED DESCRIPTION
[0080] The composition of the present invention is described in more detail below. In this specification, the term sheet also includes the concept of film. In addition, in this specification, even if described as film, it also includes the concept of sheet.
[0081] In this specification, unless otherwise specified, a numerical range includes the lower limit and the upper limit.
[0082] The varnish to which the present invention relates contains polymer compounds and monomer components that meet specific conditions. More specifically, it is preferred that it does not substantially contain components (solvent components, etc.) other than the polymer compounds and monomer components (i.e., a varnish formed by the polymer compounds and monomer components). Therefore, in this specification, when recording the manner in which the varnish may contain the polymer compounds and monomer components, the proportion (Japanese: external cutting) other than the content of other components (for example, adding some amount in an external additional manner relative to 100 parts by mass of the varnish) is considered. In other words, only the proportion of the polymer compound and the monomer component (or, the multifunctional monomer included as an essential component of the monomer component, and the monofunctional monomer that can be included arbitrarily) is considered in the composition details. In this varnish, the content of the multifunctional monomer can be more than 31% by mass and less than 70% by mass of the total mass of the varnish, preferably more than 35% by mass and less than 60% by mass. In addition, this varnish does not substantially contain a solvent component (its detailed definition is described below).
[0083] <Polymer Compound Having Radically Reactive Functional Group>
[0084] The polymer compound contained in this varnish has multiple free radical reactive functional groups (i.e., functional groups that can be cross-linked by free radicals) in the molecule. As the free radical reactive functional group, preferably one or more of the group consisting of vinyl, vinylidene, and allyl can be exemplified, and vinyl is particularly preferred. From the viewpoint of making the viscosity of the varnish reach a low viscosity suitable for operations such as impregnation and coating, the molecular weight of the polymer compound with free radical reactive functional groups can be 500 to 12,000 or 500 to less than 12,000 in terms of number average molecular weight (Mn), preferably 500 to 5,000 or 500 to less than 5,000. In this specification, the number average molecular weight is defined as the molecular weight obtained by GPC (gel permeation chromatography; gel permeation chromatography) method and converted to standard polystyrene.
[0085] As a polymer compound having a free radical reactive functional group, the following olefin-aromatic vinyl compound-aromatic polyene copolymer can be cited, but as another example, a polyether resin (including polyphenylene ether, polyether (ketone)) having a styrene group, a (meth) acrylic group, and an allyl group can be cited. Such a polymer can be obtained from SABIC under the trade name "SA9000" and from Mitsubishi Gas Chemical under the trade name "OPE-2St". In addition, it can also be obtained from Asahi Chemical Corporation and JSR Corporation. In addition, a polymer compound having a 1,2-butadiene structure in the molecule can also be used as a polymer compound having a free radical reactive functional group. As such a polymer compound, 1,2-polybutadiene of Nippon Soda Co., Ltd. and the trade name "Ricon" of Cray Valley Co., Ltd. can be exemplified. In addition, as the polymer compound, a styrene-1,2-polybutadiene copolymer having a random or block copolymer structure can also be preferably used. The content of the polymer compound in the present varnish may be 30% by mass or more and 69% by mass or less, and preferably 40% by mass or more and 65% by mass or less, based on the total mass of the varnish.
[0086] <Monomer Components>
[0087] For the monomer components contained in this varnish, the monomer types as its constituent elements can be one or more, and they are liquid at room temperature (25°C). That is, when there are multiple constituent elements of the monomer component, the overall monomer component can be liquid at room temperature. That is, when all the constituent elements of the monomer component are single components, it is not necessary to be liquid at room temperature, and a part of the monomer components that are solid at room temperature can also be included. The molecular weight of the monomer types contained in this monomer component (in the case of multiple types, all) is 300 or less, preferably 200 or less. This monomer component can contain a multifunctional monomer as an essential component and a monofunctional monomer as an optional additional component. As a mixing ratio in the monomer component, the multifunctional monomer can be greater than 50% by mass and less than 100% by mass, and (when the remainder is included) the remainder is a monofunctional monomer. The boiling point of each monomer component at atmospheric pressure can be preferably above 130°C, more preferably above 150°C, and most preferably above 180°C.
[0088] In addition, the above-mentioned monomer components have a radical reactive functional group in the molecule. Therefore, it should be noted that solvents (organic solvents) such as toluene and mesitylene are not included in the monomer components.
[0089] <Multifunctional Monomer>
[0090] The multifunctional monomer contained in the above-mentioned monomer component is a monomer having a molecular weight of 300 or less and having multiple free radical reactive functional groups in the molecule. The multifunctional monomers are preferably each liquid at room temperature (25°C), but in the case of containing multiple multifunctional monomers, as long as it is liquid as a whole at room temperature (25°C). As a multifunctional monomer, preferably ortho, meta, or para divinylbenzene or a mixture thereof (wherein, the case of only divinylbenzene monomer is not included) can be cited. For example, a commercially available divinylbenzene reagent of a mixture of meta: para (mass ratio) = 60 to 80: 20 to 40 can be used. The boiling point of these divinylbenzenes at atmospheric pressure is above 180°C. In addition, as a multifunctional monomer, BVPE (bisvinylphenyl ethane) (for example, see Japanese Patent Publication No. 2003-012710) which can contain various isomers can also be cited. BVPE has a boiling point of 200°C or more. In particular, a method for producing a liquid BVPE at room temperature is described in Japanese Patent Application Publication No. 2003-105036. As described above, the polyfunctional monomer may be 31% to 70% by mass, preferably 35% to 60% by mass, and more preferably 35% to 50% by mass, of the total mass of the varnish.
[0091] It should be noted that the polyfunctional monomer generally does not contain a bismaleimide compound. This is because the bismaleimide compound is solid at room temperature although it has a carbonyl group, which is one of the radical reactive functional groups.
[0092] <Monofunctional Monomer>
[0093] The monofunctional monomer that the above-mentioned monomer component may contain is a monomer having a molecular weight of 300 or less and having one free radical reactive functional group in the molecule, and may be liquid or solid at room temperature (25°C) (that is, the monomer component as a whole may be liquid at room temperature (25°C)). As the monofunctional monomer, preferably one or more selected from styrene, ethylvinylbenzene, and acenaphthylene can be cited. The boiling point of styrene at atmospheric pressure is 145°C, ethylvinylbenzene is 189°C, and acenaphthylene is 280°C. As a proportion in the monomer component, the monofunctional monomer may be 50% by mass or less and less than 50% by mass. In addition, as a proportion in the varnish, for example, the monofunctional monomer may be 0% by mass or more and 40% by mass or less, 0% by mass or more and less than 40% by mass, preferably 0% by mass or more and 35% by mass or less, 0% by mass or more and less than 35% by mass, more preferably 0% by mass or more and 20% by mass or less, 0% by mass or more and less than 20% by mass. When the amount of the monofunctional monomer is 40% by mass or less, the elastic modulus of the obtained cured product at high temperature tends to be high.
[0094] <Olefin-aromatic vinyl compound-aromatic polyene copolymer>
[0095] The olefin-aromatic vinyl compound-aromatic polyene copolymer that can be used as the polymer compound may preferably be a copolymer that satisfies all of the following conditions (1) to (4).
[0096] (1) The number average molecular weight of the copolymer is 500 or more and 12,000 or less, preferably 500 or more and less than 12,000.
[0097] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0 to 98% by mass.
[0098] (3) The aromatic polyene monomer unit is one or more selected from polyenes having a carbon number of 5 to 20 and having a plurality of vinyl and / or vinylidene groups in the molecule, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene monomer unit is 2 to 30 or 2 to less than 30, preferably 20 to less or less than 20, based on the number average molecular weight.
[0099] (4) It may contain one or more selected from olefin monomer units having 2 to 20 carbon atoms, and when aromatic vinyl compound monomer units and aromatic polyene monomer units are present, the total of the olefin monomer units and the aromatic polyene monomer units is 100% by mass.
[0100] The number average molecular weight (Mn) of the copolymer is 500 to 12,000 or 500 to less than 12,000, preferably 500 to 5,000 or 500 to less than 5,000.
[0101] In the present copolymer, the aromatic vinyl compound monomer may be an aromatic vinyl compound having 8 to 20 carbon atoms, and examples thereof include styrene, p-methylstyrene, p-isobutylstyrene, various vinylnaphthalenes, and various vinylanthracenes.
[0102] In this copolymer, the so-called olefin monomer is one or more selected from alpha olefins with a carbon number of 2 or more and 20 or less and cyclic olefins with a carbon number of 5 or more and 20 or less. The olefin monomer is preferably a compound consisting of carbon and hydrogen (i.e., 99% by mass or more of carbon and hydrogen, preferably a compound consisting of only carbon and hydrogen) that is substantially free of oxygen, nitrogen, and halogen. As alpha olefins with a carbon number of 2 or more and 20 or less, for example, ethylene, propylene, 1-butene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 4-methyl-1-pentene, and 3,5,5-trimethyl-1-hexene can be exemplified. As cyclic olefins with a carbon number of 5 or more and 20 or less, norbornene and cyclopentene can be exemplified. Preferably, olefins can be used as a combination of ethylene and alpha olefins other than ethylene and cyclic olefins, or ethylene alone.
[0103] As an aromatic polyene monomer, it is a polyene with a carbon number of 5 or more and 20 or less having multiple vinyl and / or vinylidene groups in its molecule, and it can be preferably various divinylbenzenes in the ortho, meta, and para positions or mixtures thereof, divinylnaphthalene, divinylanthracene, p-2-propylene styrene, p-3-butylene styrene and other compounds with aromatic vinyl structures. The aromatic polyene monomer is preferably a compound consisting of carbon and hydrogen that is substantially free of oxygen, nitrogen, and halogen (that is, 99% by mass or more is formed by carbon and hydrogen, preferably a compound formed only by carbon and hydrogen). In addition, the bifunctional aromatic vinyl compounds described in Japanese Patent Publication No. 2004-087639, such as 1,2-bis(vinylphenyl)ethane (abbreviated as: BVPE), can also be used. Among them, various divinylbenzenes in the ortho, meta, and para positions, or mixtures thereof are preferably used, and a mixture of m-divinylbenzene and p-divinylbenzene is most preferably used. In this specification, these divinylbenzenes are recorded as divinylbenzenes. When divinylbenzenes are used as the aromatic polyene, curing efficiency is high and curing is easy during curing treatment.
[0104] The content of the aromatic vinyl compound monomeric unit contained in this copolymer can be 0 mass % or more and 98 mass % or less, more preferably 10 mass % or more and 70 mass % or less. When the content of the aromatic vinyl compound monomeric unit is 98 mass % or less, the glass transition temperature of the cured product of the composition finally obtained is lower than near room temperature, and the toughness and elongation at low temperatures can be improved, so it is preferred. If the content of the aromatic vinyl compound monomeric unit is 0 mass % or more, the following effects can be obtained: the aromaticity of this copolymer is improved, the affinity with flame retardants and fillers becomes better, the exudation of flame retardants can be avoided, and the filling property of fillers can be improved. In addition, if the content of the aromatic vinyl compound monomeric unit is 0 mass % or more, the cured product of the composition with high bonding strength to copper foil and copper wiring can also be obtained.
[0105] In the present copolymer, the content of vinyl and / or vinylidene groups (preferably the content of vinyl groups) derived from the aromatic polyene unit can be 2 or more and 30 or less than 30, more preferably 20 or less than 20, and further preferably 3 or more and 20 or less than 20, in terms of unit number average molecular weight. If the content of vinyl and / or vinylidene groups is 2 or more, the crosslinking efficiency is high, and a cured product with a sufficient crosslinking density can be easily obtained. The vinyl content derived from the aromatic polyene unit (divinylbenzene unit) in the copolymer in terms of unit number average molecular weight can be obtained by the following method: the number average molecular weight (Mn) calculated by the GPC (gel permeation chromatography) method known to those skilled in the art is calculated by using the method of obtaining the crosslinked vinyl group from the aromatic polyene unit (divinylbenzene unit) and the number average molecular weight (Mn) calculated by using the method of obtaining the crosslinked vinyl group from the aromatic polyene unit (divinylbenzene unit) can be obtained by the method of obtaining the crosslinked vinyl group from the aromatic polyene unit (divinylbenzene unit) by using ... 1 H-NMR measurement and / or measurement in quantitative mode 13 The composition obtained by C-NMR measurement is compared with the vinyl content from the aromatic polyene unit. Such a method is obvious and known to those skilled in the art. In addition, the method described in the patent literature of the prior art literature of this specification can also be used.
[0106] In this copolymer, the content of the preferred olefin monomer unit is 10% by mass or more, more preferably 20% by mass or more. The total of the aforementioned olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100% by mass. If the content of the olefin monomer unit is 10% by mass or more, the toughness (elongation) and impact resistance of the finally obtained cured product are improved, and the cracking during the curing and the cracking of the cured product in the thermal cycle test are not easy to occur.
[0107] Examples of the olefin-aromatic vinyl compound-aromatic polyene copolymer include ethylene-styrene-divinylbenzene copolymer, ethylene-1-octene-divinylbenzene copolymer, ethylene-norbornene-divinylbenzene copolymer, ethylene-propylene-styrene-divinylbenzene copolymer, ethylene-1-hexene-styrene-divinylbenzene copolymer, ethylene-1-octene-styrene-divinylbenzene copolymer, and norbornene-styrene-divinylbenzene copolymer.
[0108] In the present varnish, the content of the olefin-aromatic vinyl compound-aromatic polyene copolymer may be in the range of 30% by mass or more and 69% by mass or less, and may more preferably be in the range of 40% by mass or more and 65% by mass or less. If the olefin-aromatic vinyl compound-aromatic polyene copolymer is 30% by mass or more, the effect of not easily showing brittleness in the obtained cured product can be obtained, and if it is 69% by mass or less, the effect of easily improving the elastic modulus at high temperature and easily satisfying the required characteristics of a rigid substrate, etc. can be obtained.
[0109] In a preferred embodiment, the monomer component contained in the varnish may be divinylbenzene, and its content may be 30% or more or greater than 30% and less than 69% by mass of the total mass of the varnish. If divinylbenzene is more than 30% by mass, it has the effect of appropriately suppressing the viscosity of the varnish, or the crosslinking density of the obtained cured product, and the elastic modulus in the high temperature region becoming appropriate. In addition, if divinylbenzene is less than 69% by mass, the effect of becoming less likely to show brittleness in the obtained cured product can be obtained. According to such a preferred embodiment, it is easy to obtain a cured product that is particularly suitable as an insulating layer of a rigid substrate, has a sufficiently high crosslinking density and a low linear expansion coefficient, and has a high elastic modulus in the high temperature region. Specifically, it is easy to obtain a cured product having a linear expansion coefficient of less than 100ppm / °C, and a storage modulus (E') of more than 20MPa, preferably more than 30MPa, at 280°C measured by DMA (dynamic viscoelasticity determination method).
[0110] In one embodiment, the varnish may contain (in other proportions) one or more selected from the following (a) or (b).
[0111] (a) Curing agent
[0112] (b) one or more resins selected from hydrocarbon elastomers, polyether resins, and aromatic polyene resins
[0113] <Curing Agent>
[0114] As the curing agent that can be used in the varnish of the present invention, the known curing agent that can be used in the polymerization or curing of the previous aromatic polyene and aromatic vinyl compound can be used. As such a curing agent, free radical polymerization initiators (free radical generators), cationic polymerization initiators, and anionic polymerization initiators can be exemplified, and free radical polymerization initiators can be preferably used. More preferably, organic peroxides (peroxides), azo polymerization initiators, etc. can be freely selected according to the purpose and conditions. The product catalog of organic peroxides can be downloaded from the homepage of NOF Corporation, such as https: / / www.nof.co.jp / product-search / family / 1020001. In addition, organic peroxides are also recorded in the product catalogs of Fujifilm and Koko Pure Chemical Industries, Ltd. and Tokyo Chemical Industry Co., Ltd. The curing agent used in the present invention can be obtained from these companies. In addition, known photopolymerization initiators using light, ultraviolet rays, and radiation can also be used as curing agents. As photopolymerization initiators, photoradical polymerization initiators, photocationic polymerization initiators, or photoanionic polymerization initiators can be cited. Such a photopolymerization initiator can be obtained from, for example, Tokyo Chemical Industry Co., Ltd. In addition, curing can also be performed by radiation or electron beam itself. In addition, crosslinking and curing can also be performed by thermal polymerization of the contained raw materials without containing a curing agent.
[0115] The amount of the curing agent used is not particularly limited. Generally, it is preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the varnish of the present invention. As for the resin composition, it is preferred to remove the curing agent and the solvent. When using a curing agent such as a peroxide or azo polymerization initiator, the curing treatment is performed at an appropriate temperature and time in consideration of its half-life. The conditions in this case are arbitrary depending on the curing agent. Generally, a temperature range of about 50°C to 200°C is appropriate.
[0116] In addition, when used in the varnish of the present invention, the amount of the component (b) is preferably within a range that can maintain a liquid state at room temperature, preferably 20 parts by mass or less, and more preferably 10 parts by mass or less relative to 100 parts by mass of the varnish of the present invention. By adding these components (b), the mechanical properties of the cured product obtained from the varnish at room temperature can be improved.
[0117] <Hydrocarbon-based elastomer>
[0118] The number average molecular weight of the hydrocarbon elastomer that can be preferably used in the composition of the present invention is preferably 100 or more and 100,000 or less, more preferably 1000 or more and 4500 or less. As the hydrocarbon elastomer that can be preferably used in the composition of the present invention, it is preferably selected from one or more elastomers in ethylene-based, propylene-based elastomers, conjugated diene polymers, aromatic vinyl compound-conjugated diene block copolymers or random copolymers, and their hydrogenates (hydrogenated products). As ethylene-based elastomers, ethylene-alpha olefin copolymers such as ethylene-octene copolymers and ethylene-1-hexene copolymers, EPR, EPDM, etc. can be cited. As propylene-based elastomers, propylene-alpha olefin copolymers such as atactic polypropylene, polypropylene with low stereoregularity, propylene-1-butene copolymers, etc. can be cited. For these hydrocarbon-based elastomers, modifications such as introducing functional groups by maleic anhydride and other compounds can be carried out. The composition according to another embodiment also preferably does not substantially contain a hydrocarbon-based elastomer containing other elements such as oxygen atoms and / or other optional added components described below (carbon and hydrogen account for 99% by mass or more).
[0119] As conjugated diene polymers, polybutadiene, 1,2-polybutadiene, etc. can be cited. As block polymers or random copolymers of aromatic vinyl compounds-conjugated dienes, and their hydrogenated products (hydrogenated products), SBS, SIS, SEBS, SEPS, SEEPS, SEEBS, etc. can be exemplified. 1,2-Polybutadiene that can be preferably used can be obtained, for example, from Nippon Soda Co., Ltd. as liquid polybutadiene: product names B-1000, 2000, 3000. In addition, as a copolymer containing a 1,2-polybutadiene structure that can be preferably used, "Ricon100" of Total Cray Valley can be exemplified. These conjugated diene polymers and their hydrogenated products can be modified by introducing functional groups using maleic anhydride or other compounds. One or more resins selected from these hydrocarbon elastomers are preferably liquid (about 300,000 mPa·s or less) at room temperature (25°C), especially from the viewpoint of the handleability and molding processability (handleability as a thermoplastic resin) of the composition of the present invention in the uncured state.
[0120] <Polyether resin>
[0121] As polyether resins, polyphenylene ether and polyether can be cited. As polyphenylene ether having a functional group, it is preferred that the molecular end is modified by a functional group. As polyphenylene ether (also referred to as "polyphenylene ether resin"), commercially available known polyphenylene ether can be used. The number average molecular weight of the polyphenylene ether is arbitrary. If the molding processability of the composition is taken into consideration, the number average molecular weight is preferably less than 10,000, and most preferably less than 5,000. The number average molecular weight is preferably 500 or more.
[0122] In addition, in the case of addition for the purpose of curing the composition of the present invention, the polyether resin preferably has a functional group modified at the molecular end. In addition, in the case of addition for the purpose of curing the composition of the present invention, it is preferred to have multiple functional groups in one molecule. As a polyether resin, for example, a modified polyphenylene ether is preferred. As a functional group, free radical polymerizable functional groups, epoxy groups and other functional groups can be cited, preferably free radical polymerizable functional groups. As a free radical polymerizable functional group, a vinyl group is preferred. As a vinyl group, it is preferably one or more of the group consisting of allyl, (meth) acryloyl, and aromatic vinyl, more preferably one or more of the group consisting of (meth) acryloyl and aromatic vinyl, and most preferably aromatic vinyl. That is, in the composition of the present invention, it is particularly preferred that the two ends of the molecular chain are modified with free radical polymerizable functional groups. As such polyphenylene ether, Noryl (trademark) SA9000 (a modified polyphenylene ether having methacryloyl groups at both ends, with a number average molecular weight of 2200) manufactured by SABIC, a difunctional polyphenylene ether oligomer (OPE-2St, a modified polyphenylene ether having vinyl benzyl groups at both ends, with a number average molecular weight of 1200) manufactured by Mitsubishi Gas Chemicals, etc. can be cited. In addition, allyl PPE manufactured by Asahi Kasei Corporation and aromatic polyethers (ELPAC HC-F series) manufactured by JSR Corporation can also be used. Among these, the difunctional polyphenylene ether oligomer (OPE-2St) manufactured by Mitsubishi Gas Chemicals, Inc. can be preferably used.
[0123] <Aromatic polyene resin>
[0124] So-called aromatic polyene resins include divinylbenzene reactive multibranch copolymers (PDV or ODV) made by NIPPON STEEL Chemical & Material Co., Ltd. Such PDV is, for example, recorded in the document "Synthesis of multifunctional aromatic vinyl copolymers and development of novel IPN type low dielectric loss materials using them" (Masanori Kawabe, Journal of Japan Institute of Electronics Packaging p125, Vol. 12 No. 2 (2009)). In order to prevent the adhesion and toughness of other components from decreasing, the use of aromatic polyene resins is preferred. The number average molecular weight of aromatic polyene resins is arbitrary. If the molding processability of the composition is taken into account, the number average molecular weight is preferably less than 10,000, and most preferably less than 5000. The number average molecular weight is more than 500.
[0125] The present varnish may further contain one or more selected from the following (c) to (f) (in other proportions).
[0126] (c) Polar monomers
[0127] (d) Fillers
[0128] (e) Flame retardant
[0129] (f) Surface modifier
[0130] <Polar Monomer>
[0131] The usage amount of the polar monomer that the varnish composition of the present invention can include can be less than 10 mass parts in proportion to 100 mass parts of varnish. By using the amount of this range, the dielectric constant and dielectric loss tangent of the obtained solidified body can be obtained without becoming too high, for example, the dielectric constant can be suppressed to less than 4.0, preferably less than 3.0, and the dielectric loss tangent can be suppressed to less than 0.003, preferably less than 0.002. It should be noted that this resin composition can be substantially free of polar monomers. The so-called polar monomer is a monomer having one or more atoms selected from oxygen, nitrogen, phosphorus, and sulfur in the molecule, and the molecular weight of the polar monomer that can be preferably used is preferably less than 5000 or less than 5000, more preferably less than 1000 or less than 1000, and further preferably less than 500 or less than 500. The polar monomer that can be preferably used in the resin composition of the present invention is preferably a polar monomer that can be polymerized using a free radical polymerization initiator. As polar monomers, various maleimides, bismaleimides, maleic anhydride, triallyl isocyanurate, glycidyl (meth)acrylate, tri(meth)acrylate isocyanurate, trimethylolpropane tri(meth)acrylate, etc. can be cited. Maleimides and bismaleimides that can be used in the present invention are described in, for example, International Publication No. 2016 / 114287 and Japanese Patent Publication No. 2008-291227, and can be purchased from, for example, Yamato Chemical Industry Co., Ltd., Nippon Kayaku Co., Ltd., and Designer molecules inc. In addition, bismaleimide resin "SLK" manufactured by Shin-Etsu Chemical Co., Ltd. can also be used. From the viewpoints of solubility in organic solvents, high-frequency characteristics, high adhesion to conductors, and prepreg formability, these maleimide-containing compounds are preferably bismaleimides. From the viewpoints of solubility in organic solvents, high frequency characteristics, high adhesion to conductors, formability of prepregs, etc., these compounds containing maleimide groups can also be used as polyaminobismaleimide compounds. Polyaminobismaleimide compounds can be obtained, for example, by subjecting a compound having two maleimide groups at the end to a Michael addition reaction with an aromatic diamine compound having two primary amino groups in the molecule. In the case where a high crosslinking efficiency is desired to be obtained by a small amount of addition, a polar monomer having a multifunctional group of more than two functional groups is preferably used. As polar monomers having a multifunctional group of more than two functional groups, bismaleimides, triallyl isocyanurate (TAIC), trimethylolpropane tri(meth)acrylate, etc. can be exemplified.
[0132] <Filling Agent>
[0133] As required, known inorganic or organic fillers can be added. These fillers are added for the purpose of controlling the coefficient of thermal expansion, controlling thermal conductivity, and low price, and their usage amount is arbitrary according to the different purposes. Especially when adding inorganic fillers, it is preferred to use known surface modifiers, such as silane coupling agents, etc. Especially in the case of resin compositions with low dielectric constant and low dielectric loss as one of the purposes of the present invention, as inorganic fillers, it is preferably one or more of boron nitride (BN) or silicon dioxide, more preferably silicon dioxide. As silicon dioxide, it is preferably fused silica. From the viewpoint of the viscosity of varnish, if a large amount of addition is made, the viscosity becomes high, so it is possible to use a filler preferably less than 200 mass parts or less than 200 mass parts, more preferably less than 100 mass parts or less than 100 mass parts, in proportion relative to 100 mass parts of the varnish of the present invention. Furthermore, in order to improve and enhance low dielectric properties (low dielectric constant, low dielectric loss tangent), a hollow filler or a filler having a shape with many voids may be added.
[0134] <Flame retardant>
[0135] Flame retardants can be used in the composition of the present invention. From the viewpoint of maintaining a low dielectric constant and a low dielectric loss tangent, preferred flame retardants are known organic phosphorus-based flame retardants such as phosphate esters or their condensates, known bromine-based flame retardants, and red phosphorus. In particular, among phosphate esters, compounds having a plurality of xylene groups in the molecule are preferred from the viewpoint of flame retardancy and low dielectric loss tangent.
[0136] In addition, in addition to flame retardants, antimony compounds such as antimony trioxide, antimony tetroxide, antimony pentoxide, sodium antimonate, or nitrogen-containing compounds such as melamine, triallyl-1,3,5-triazine-2,3,4-(1H,3H,5H)-trione, 2,4,6-triallyloxy-1,3,5-triazine may be added as flame retardant aids. The total amount of these flame retardants and flame retardant aids is usually preferably 1 to 100 parts by mass relative to 100 parts by mass of the varnish of the present invention. In addition, 30 to 200 parts by mass of the aforementioned polyphenylene ether (PPE)-based resins with low dielectric constant and excellent flame retardancy may be used relative to 100 parts by mass of the flame retardant.
[0137] <Surface Modifier>
[0138] The varnish of the present invention may contain a surface modifier for the purpose of improving adhesion to the copper foil for wiring. The purpose is particularly to improve the bonding strength (peel strength) to the smooth surface of the copper foil. The amount of the surface modifier used can be in the range of 0.001 to 10 parts by mass, more preferably in the range of 0.01 to 5 parts by mass, and most preferably in the range of 0.01 to 1 part by mass relative to 100 parts by mass of the olefin-aromatic vinyl compound-aromatic polyene copolymer. If the amount of the surface modifier used is less than 10 parts by mass, the dielectric constant and dielectric loss tangent of the cured body obtained from the composition become lower. In the present invention, known surface modifiers can be used. As such a surface modifier, silane-based surface modifiers (also known as silane coupling agents), carbonate-based surface modifiers, and isocyanate-based surface modifiers can be cited, and silane-based surface modifiers are preferably used. One or more of these surface modifiers can be used. Such silane-based surface modifiers are available from Shin-Etsu Chemical Co., Ltd., Dow Corning, and Evonik.
[0139] It should be noted that, as described above, although it is described that the varnish may contain components (a) to (f), it is particularly preferred that the varnish does not substantially contain any of the components (a) to (f). These components (a) to (f) can be used by those skilled in the art within the aforementioned range relative to the varnish as needed. In other words, it can be considered that in one embodiment of the present invention, a composition comprising the above-mentioned varnish that does not substantially contain any of the components (a) to (f), and any of the components (a) to (f) in a proportion other than that relative to the varnish can be provided.
[0140] <Solvent>
[0141] In one embodiment, the varnish is preferably substantially free of solvent components (solvent). Here, the so-called substantially free of solvent components means that the content of the solvent component is less than 2% by mass, less than 2% by mass, preferably less than 1% by mass, less than 1% by mass, more preferably less than 0.5% by mass, less than 0.5% by mass, and more preferably substantially zero. If the varnish is substantially free of solvent components, it will not foam during curing, and the swelling and bulging of the circuit substrate will not occur. For the varnish of the present invention, liquid monomer components, particularly multifunctional monomer components are used instead of being substantially free of solvent, so that the fluidity as a varnish can be presented. In another embodiment, as described later, a varnish containing a solvent component can also be provided.
[0142] In addition, the varnish of the present invention may contain additives commonly used for resins, such as antioxidants, weathering agents, light stabilizers, lubricants, compatibilizers, antistatic materials, etc., within the range that does not hinder the effects and purposes of the present invention. The composition and varnish of the present invention can be obtained by mixing and dissolving the various raw materials and additives mentioned above, and any known method can be used as the mixing and dissolving method.
[0143] <Varnish>
[0144] The varnish of the present invention can be in liquid state at room temperature due to the above-mentioned structure. The viscosity of the varnish is, for example, less than tens of thousands of mPa·s at 25°C, preferably less than 5000 mPa·s in the state without filler, and more preferably less than 2000 mPa·s. Specifically, the varnish can be coated, impregnated, filled or dripped onto other raw materials by appropriate methods, and heated and pressurized to be cured, thereby forming a molded body of the cured product. For such properties, various transfer molding (press molding) can be performed, or it can be coated on or between substrates, semiconductor device materials, or coated on sheets or films by extrusion lamination or spin coating and then cured, thereby forming an insulating film or insulating layer. In addition, a varnish substantially free of solvent components can be obtained by distilling off most of the solvent and residual monomers from the polymerization liquid obtained by copolymerizing the above-mentioned olefin-aromatic vinyl compound-aromatic polyene copolymer (usually, in addition to the copolymer, a solvent used in the polymerization such as toluene, ethylbenzene, cyclohexane, methylcyclohexane, residual monomers such as styrene and divinylbenzene, residual monomers such as olefin monomers, catalysts, and co-catalyst components) under reduced pressure, and diluting with liquid monomer components. That is, the varnish of the present invention may contain a part of the residual monomers during polymerization as monomer components.
[0145] In another embodiment, the varnish of the present invention can also be obtained by the following method. That is, the following varnish is prepared: it contains an olefin-aromatic vinyl compound-aromatic polyene copolymer (for example, an olefin-aromatic vinyl compound-aromatic polyene copolymer that satisfies the above-mentioned conditions (1) to (4)) and a monomer component containing a multifunctional monomer that is liquid at room temperature, and contains a relatively small amount of a relatively volatile solvent component. Here, the so-called "relatively small amount of solvent component" refers to a solvent component that is preferably less than the monomer component containing a multifunctional monomer that is liquid at room temperature. In addition, the so-called "relatively volatile solvent component" is a solvent component whose boiling point under atmospheric pressure is lower than that of the contained multifunctional monomer component by more than 30°C, preferably by more than 50°C. As a preferred combination example, for example, divinylbenzene is used as the multifunctional monomer component and toluene is used as the solvent component. By subjecting the present varnish to a selective solvent removal step, a varnish having a composition that is substantially free of solvent components can be obtained, and the cured body of the present invention can also be obtained by curing it. Here, the so-called "selective solvent removal process" is a process for selectively removing the solvent component by appropriately adjusting the conditions such as temperature, pressure, and flow rate of air-drying gas. Although there is a case where the monomer component including the multifunctional monomer is also lost together with the solvent component to some extent, by appropriately controlling the conditions, a varnish substantially free of solvent components can be obtained according to the present invention. That is, even if a solvent is initially contained, after the selective solvent removal process, a composition of a varnish substantially free of solvent can be obtained, and by curing it, a cured product of the present invention can be obtained.
[0146] The cured product of the varnish can be used as the crosslinked resin matrix. The crosslinked resin matrix is preferably a substance consisting essentially of carbon and hydrogen (containing 99% by mass or more of carbon and hydrogen), and more preferably only consisting of carbon and hydrogen.
[0147] The storage modulus of the cured or cross-linked resin matrix at 25°C may be 80 MPa or more, more preferably 80 MPa or more and 2000 MPa or less. In addition, the storage modulus of the cured or cross-linked resin matrix at 280°C may be 30 MPa or more, more preferably 30 MPa or more and 1000 MPa or less.
[0148] In one embodiment, a method for manufacturing a solidified body (or a cross-linked resin matrix) may also be provided. The manufacturing method comprises:
[0149] a step of preparing a varnish comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer and a multifunctional monomer component; and
[0150] A step of obtaining a cured product having a storage elastic modulus of 80 MPa or more at 25° C. and a storage elastic modulus of 30 MPa or more at 280° C. by curing the varnish.
[0151] When the varnish contains a solvent component, the production method may further include a step of selectively removing the solvent component.
[0152] <Molding and curing>
[0153] The shape of the molded body and cured body obtained by the varnish of the present invention is arbitrary. For example, by coating on a substrate, or by being impregnated with cloth such as glass fiber, nonwoven fabric, etc., a porous substrate, and then stacked and coated with copper foil and substrate, and heated and cured under pressure, a single-layer or multi-layer substrate can be made. The varnish of the present invention and the molded body obtained by them can be cured by a known method with reference to the curing conditions (temperature, time, pressure) of the raw materials and curing agents included. When the curing agent used is a peroxide, the curing conditions can be determined with reference to the half-life temperature disclosed for each peroxide. Curing can be one stage or multiple stages. In particular, curing is carried out in multiple stages, and a molded body (prepreg) in a semi-cured state can also be passed through in the middle. In particular, the sheet can be a semi-cured state of the degree that can maintain the shape of the sheet, or it can be fully cured after being stacked with other substrates and copper foil. In order to achieve a semi-cured state, examples include a method of adjusting the amount of the aforementioned curing agents with different half-life temperatures and using them together, a method of appropriately adjusting the curing time and / or curing temperature, or a method of changing the curing mode (for example, using light curing for semi-curing, using peroxide for formal curing, etc.). The conventional solvent drying process can also be applied to such a semi-curing process. Alternatively, when curing is performed by heating and pressurizing with a press, by making the heating conditions multi-stage, a semi-cured state can also be introduced in the middle of this process to inhibit the exudation of varnish and the occurrence of uneven thickness. The degree of curing of the molded body, especially the sheet, can be quantitatively measured using the known dynamic viscoelasticity determination method (DMA, Dynamic Mechanical Analysis).
[0154] <Base material for impregnation>
[0155] As the base material impregnated with the varnish of the present invention, fiber base materials known for substrates such as glass fiber, polyamide fiber, and alumina fiber can be cited. The use of various coupling agents for improving the affinity with these fibers is also known. In addition, fluororesins such as porous PTFE can also be used.
[0156] <Cured body obtained from the varnish of the present invention, and cured body of the molded body>
[0157] The cured body obtained by the varnish of the present invention is fully cured, and the gel fraction measured according to ASTM is preferably 90% by mass or more. In addition, the average dielectric constant of the cured body in the measurement range of 10 to 50 GHz, particularly preferably in the measurement range of 20 to 42 GHz, is preferably 3.0 or less and 2.0 or more, more preferably 2.8 or less and 2.0 or more, and most preferably 2.5 or less and 2.0 or more. The average dielectric loss tangent is preferably 0.0020 or less and 0.0003 or more, more preferably 0.0015 or less and 0.0003 or more, and most preferably 0.0012 or less and 0.0003 or more. It is further preferred that in the measurement range of 20 to 42 GHz, the average dielectric constant can be 3.0 or less and 2.0 or more, and the average dielectric loss tangent can be 0.0012 or less and 0.0003 or more. Thus, the cured body obtained by the varnish of the present invention is particularly preferred as an electrical insulating material for high frequencies such as 10 GHz or more due to its low dielectric loss tangent value.
[0158] In addition, the solidified body obtained from the varnish of the present invention can present a storage modulus of 50 MPa or more, preferably 80 MPa or more, at room temperature (25°C) without a filler (filler), and has sufficient strength. As a substrate, a further high storage modulus can be achieved by further adding a filler, but by using a solidified body obtained from the varnish of the present invention, the amount of filler used to achieve the elastic modulus required as a substrate can be reduced. Adding a larger amount of filler will cause the fluidity of the varnish to decrease and the molding processability to deteriorate, or increase the dielectric constant Dk of the solidified body in particular, so it is sometimes not ideal for those skilled in the art. In addition, the solidified body obtained from the varnish of the present invention can present a storage modulus of 20 MPa or more, preferably 30 MPa or more, at a high temperature (280°C) without a filler, and has sufficient strength and crosslinking density. The size of the storage modulus at high temperature corresponds to the height of the crosslinking density. A high crosslinking density indicates that the linear expansion coefficient of the solidified body is low, which is considered to be preferred in terms of ensuring the stability of the substrate at a reflow temperature such as 280°C.
[0159] The cured product obtained from the varnish of the present invention is particularly suitable as an electrical insulating material for high-frequency signals, and these cured products can be suitably used in CCL substrates, FCCL substrates, interlayer insulating materials or covering layers. In addition, the present invention can also provide a CCL substrate, FCCL substrate, interlayer insulating material or covering layer formed by the copolymer or a composition containing the copolymer. The cured product obtained from the varnish of the present invention is considered to be particularly useful as an insulating material for a packaging substrate because of its high crosslinking density.
[0160] In addition, since the varnish of the present invention does not contain a solvent component in substance, it can be preferably used as various coating inks, such as printer inks, particularly inkjet printers and 3D printer inks. As the curing method in this case, light curing (UV light curing, etc.) is preferred.
[0161] Example
[0162] Hereinafter, the present invention will be described by way of examples, but the present invention is not construed as being limited to the following examples.
[0163] The copolymers obtained in the Synthesis Examples and Comparative Synthesis Examples were analyzed by the following means.
[0164] The content of vinyl units derived from ethylene, styrene and divinylbenzene in the copolymer is determined by 1 H-NMR, measured based on the intensity of the peak area attributable to each. The sample was dissolved in deuterated 1,1,2,2-tetrachloroethane and measured at 80-130°C. When the copolymer contains α-olefin units, the quantitative mode is also used. 13 C-NMR measurement was carried out by a known method.
[0165] The molecular weight was determined by using GPC (gel permeation chromatography) to determine the number average molecular weight (Mn) in terms of standard polystyrene. The measurement was performed under the following conditions.
[0166] Chromatographic columns: 2 TSK-GEL MultiporeHXL-M (manufactured by Tosoh Corporation) are connected in series and used.
[0167] Column temperature: 40°C
[0168] Solvent: THF
[0169] Liquid delivery flow rate: 1.0ml / min
[0170] Detector: RI detector
[0171] <Viscosity>
[0172] The viscosity of the copolymer obtained in each of Examples and Comparative Examples was determined as follows.
[0173] A 50 mass % toluene solution of each copolymer was prepared and measured using a rotational rheometer (MCR302: manufactured by Anton Paar) at 25°C with a shear rate of 1 second. -1 The value of .
[0174] <Gel Fraction>
[0175] The gel fraction as a boiling toluene insoluble component was determined in accordance with ASTM D2765-84.
[0176] <Water absorption>
[0177] The water absorption rate after immersion in pure water at 23° C. for 24 hours was measured in accordance with ASTM D570-98.
[0178] <Dielectric constant and dielectric loss (dielectric loss tangent)>
[0179] As for the dielectric constant and dielectric loss tangent, a balanced disk resonator (manufactured by Keysight Technologie) was used to evaluate the dielectric properties. The method for evaluating the dielectric properties using a balanced disk resonator is as follows: prepare two identical samples (diameter 3 cm, thickness 0.2 to 0.6 mm), sandwich a copper foil between them and place them in the resonator, and measure the resonance frequency f0, no-load Q, and Qu of the peak that appears at 20 to 42 GHz. Using the analysis software attached to the resonator (Balanced type circular disk resonator (method) calculator, balanced disk resonator method analysis software), the dielectric constant is calculated from f0, the dielectric loss tangent (tanδ) is calculated from Qu, and the average value of 20 to 42 GHz is calculated. The measurement temperature is 23°C and the humidity is 50% RH.
[0180] <Determination of Storage Modulus>
[0181] The storage modulus at 280°C was measured using a dynamic viscoelasticity measuring device (TA Instruments, formerly Rheometrics RSA-G2) at a frequency of 1 Hz while increasing the temperature from room temperature. A sample (3 mm × 40 mm) was cut out from a film with a thickness of about 0.1 to 0.3 mm, and the storage modulus was determined. The main measurement parameters related to the measurement are as follows.
[0182] Measuring frequency 1Hz
[0183] Heating rate: 3℃ / min
[0184] Sample measurement length 10mm
[0185] Strain 0.1%
[0186] <Synthesis Example; Production of Copolymer P-1>
[0187] With reference to the manufacturing method described in Japanese Patent Publication No. 2009-161743, Japanese Patent Publication No. 2010-280771, and International Publication No. 2022 / 014599, dimethylmethylenebiscyclopentadienyl zirconium dichloride (structure sees the following formula (1)) and MMAO (modified methylaluminoxane, manufactured by Tosoh Finechem) are used as catalysts, toluene is used as solvent, styrene, divinylbenzene, and ethylene are used as raw materials, and a polymerization tank with a capacity of 10L and a stirrer and a heating and cooling jacket is used for polymerization to obtain a polymerization liquid. The obtained polymerization liquid is fully put into a large amount of methanol in small amounts and multiple times, stirred and decanted, thereby obtaining a copolymer, and the obtained copolymer is thinly spread in a square flat bottom plate (vat), and fully vacuum dried at room temperature to obtain a semi-solid ethylene-styrene-divinylbenzene copolymer P-1.
[0188] Formula (1)
[0189] [Chemical formula 1]
[0190]
[0191] <Synthesis Example; Production of Copolymers P-2, P-3>
[0192] The same operation as the production of P-1 was carried out, wherein rac-diphenylmethylene (1-indenyl) (cyclopentadienyl) zirconium dichloride (structure see the following formula (2)) was used as a catalyst and the concentration of each raw material monomer, polymerization temperature and polymerization time were appropriately changed to obtain copolymers P-2 and P-3.
[0193] Formula (2)
[0194] [Chemical formula 2]
[0195]
[0196] <Synthesis Example; Production of Copolymer P-4>
[0197] With respect to the polymerization conditions of Synthesis Example 1, further reference was made to International Publication No. 2017 / 122295, where the co-catalyst was changed from MMAO to triphenylcarbonium tetrakis(pentafluorophenyl)borate {trityltetrakis(pentafluorophenyl)borate}, and the styrene monomer used was changed to a low phenylacetylene (LPA) grade having a phenylacetylene content of 17 ppm (manufactured by Denka Corporation), and ethylene, styrene and divinylbenzene were copolymerized to obtain ethylene-styrene-divinylbenzene copolymer P-4.
[0198] Table 1 shows the compositions and molecular weights of P-1 to P-4 obtained in the respective synthesis examples.
[0199] In addition, other raw materials are as follows.
[0200] Divinylbenzene (DVB) was manufactured by NIPPON STEEL Chemical & Material Co., Ltd. under the trade name "divinylbenzene (96%)" (liquid at room temperature, containing 96% by mass of divinylbenzene as a mixture of meta- and para-isomers, with the remainder being ethylvinylbenzene). In the following examples, when 35 parts by mass of this product was used, 33.6 parts by mass of divinylbenzene was used as a compound. Ethylvinylbenzene is equivalent to the monofunctional monomer of the present invention.
[0201] BVPE (bisvinylphenylethane) having a purity of 92% was used and manufactured by Changzhou Xingsheng Technology Co., Ltd. Acenaphthylene was manufactured by JFE Chemical Co., Ltd.
[0202] As the curing agent, PERBUTYL P (α,α′-di(tert-butylperoxy)diisopropylbenzene) manufactured by NOF Corporation was used.
[0203] [Table 1]
[0204]
[0205] [Table 2]
[0206] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Comparative Example 1 Comparative Example 2 Comparative Example 3 P-1 65 - - 55 - 55 - 65 50 - P-2 - 50 - - - - - - - 50 P-3 - - 60 - 40 - - - - - P-4 - - - - - - 60 - - - DVB 35 50 40 35 40 35 40 35 25 - BVPE - - - - - 10 - - - - Acenaphthylene - - - 10 - - - - - - Styrene - - - - 20 - - - 25 - OPE-2St - - - - - - - - - 50 Solvent (Toluene) Does not contain Does not contain Does not contain Does not contain Does not contain Does not contain Does not contain 3 Does not contain 100 Viscosity of varnish ο ο ο ο ο ο ο ο ο ο Curing agent 1 1 1 1 1 1 1 1 1 1 State of the solidified material ο ο ο ο ο ο ο × Foaming is present ο ο Gel fraction >95% >95% >95% >95% >95% >95% >95% Undetermined >95% >95% Storage modulus (25℃) / MPa 98 330 180 310 780 220 250 Undetermined 280 320 Storage modulus (280℃) / MPa 36 180 60 50 145 68 180 Undetermined 15 10 Dielectric constant (20~42GHz) 2.4 2.4 2.4 2.5 2.5 2.4 2.3 Undetermined 2.5 2.5 Dielectric loss tangent (20~42GHz) 0.0009 0.0011 0.0010 0.0012 0.0012 0.0012 0.0007 Undetermined 0.0013 0.0017 Water absorption (wt96) <0.1 <0.1 <0.1 <01 <0.1 <0.1 <0.1 Undetermined <0.1 <0.1
[0207] Example 1
[0208] Using a container equipped with a heating and cooling jacket and a stirring blade, 65 parts by mass of P-1 (ethylene-styrene-divinylbenzene copolymer) obtained in the synthesis example was added to 35 parts by mass of "divinylbenzene (96%)" manufactured by NIPPON STEEL Chemical & Material Co., Ltd. as divinylbenzene, heated to about 50°C and stirred to dissolve the copolymer to prepare 100 parts by mass of varnish. Then, 1 part by mass of a curing agent (PERBUTYL P, 1,4-bis[(tert-butylperoxy)isopropyl]benzene) was added in an external ratio relative to 100 parts by mass of the varnish, dissolved, stirred and mixed, and a varnish-like composition was obtained (Table 2). The obtained composition was poured into a Teflon frame (frame part length 7 cm, width 7 cm, thickness 0.2 mm, 0.5 mm or 1.0 mm) obtained by cutting a Teflon (registered trademark) plate with a thickness of 2 mm, then a Teflon plate was placed on the frame, a weight of several kg was placed to seal it, and the frame was heated at 120°C for 30 minutes, at 150°C for 30 minutes, and then at 200°C for 120 minutes, and the Teflon plate and the Teflon frame were removed to obtain a cured sheet. The gel fraction, storage modulus (25°C and 280°C), dielectric constant, dielectric loss tangent (all average values at 23°C and 20 to 42 GHz), and water absorption of the obtained cured sheet were determined.
[0209] Embodiments 2 to 7
[0210] The same operation as in Example 1 was carried out according to the formulation in Table 2 (the unit in the table is parts by mass) to obtain a cured sheet, and the physical property values were obtained in the same manner. In Example 5 and Comparative Example 2 using styrene, a low temperature curing condition was required to prevent evaporation of styrene, and PERBUTYL O (tert-butyl peroxy-2-ethylhexanoate) was used as a curing agent. The curing conditions were 85° C. and 10 hours.
[0211] Comparative Example 1
[0212] The same operation as in Example 1 was carried out, wherein 3 parts by mass of toluene was added to the varnish to prepare a varnish-like composition, and a cured sheet was obtained according to the formulation of Table 2 (the units in the table are parts by mass) in the same steps as in Example 1. However, the obtained sheet foamed violently and no further physical property measurements were performed.
[0213] Comparative Example 2
[0214] Varnishes and compositions were prepared according to the formulations shown in Table 2 (the units in the table are parts by mass), and the same procedures as in Example 1 were carried out to obtain cured sheets.
[0215] Comparative Example 3
[0216] Using P-2, according to the formulation of Table 2 (the units in the table are parts by mass), using OPE-2St as the auxiliary raw material, and using toluene as the solvent, a varnish-like composition was prepared. The composition was injected into the Teflon mold of Example 1, and dried at 60°C in a vacuum dryer for a day and night to remove the solvent toluene to obtain an uncured sheet. Multiple sheets of this sheet were overlapped and placed in the same Teflon mold, degassed under reduced pressure, and further stacked with Teflon plates, and pressurized and cured in the same manner as Example 1 to obtain a cured sheet.
[0217] Table 2 shows the viscosity of the varnish of each example and comparative example. The case where the viscosity of the varnish is 5000 mPa·s or less is recorded as 0, and the case where the viscosity of the varnish is greater than 5000 mPa·s is recorded as ×. The viscosity of the varnish of each example is 5000 mPa·s or less.
[0218] The appearance (visual observation), gel fraction, storage modulus at 25°C, storage modulus at 280°C, dielectric constant, dielectric loss tangent, and water absorption of the cured products (cured sheets, cured bodies) obtained in each example and comparative example are shown in Table 2. The case where no foaming was observed in the appearance of the cured product (state of the cured product) was marked as 0, and the case where foaming was observed in the appearance of the cured product was marked as ×.
[0219] The cured sheet obtained in the embodiment exhibits a high gel fraction, is fully cured, and exhibits a low dielectric constant and a low dielectric loss tangent value required as a high-frequency insulating material. In addition, the storage modulus exhibits sufficient hardness (storage modulus at room temperature) and mechanical strength at high temperature (high storage modulus at 280°C) as a substrate, especially a rigid substrate.
[0220] On the other hand, as shown in Comparative Example 1, if you want to use the process of removing and drying the solvent-free varnish of the present embodiment, the cured sheet will foam and a cured sheet suitable for the substrate cannot be obtained. As shown in Comparative Example 2, when the content of the multifunctional monomer is small, the elastic modulus at high temperature does not meet the benchmark of the present invention. In Comparative Example 3, OPE-2St is used instead of divinylbenzene, and a varnish is made using toluene solvent. After the solvent is dried, it is heated and cured to obtain a cured sheet, but the storage modulus of the cured sheet at 280°C is low and the mechanical strength at high temperature is insufficient. In addition, the dielectric constant and the dielectric loss tangent are all high values compared with the cured sheet of the embodiment. These results are clearer in comparison with Example 2, which also uses 50 parts by mass of P-2.
Claims
1. A varnish, characterized in that Include: A polymer compound having a plurality of free radical reactive functional groups in the molecule and having a number average molecular weight (Mn) of 500 to 12,000; and A monomer component having a free radical reactive functional group in the molecule, having a molecular weight of 300 or less and being liquid at room temperature, The monomer component contains a multifunctional monomer, and the content of the multifunctional monomer is 31 mass % or more and 70 mass % or less of the total mass of the varnish, and The varnish contains substantially no solvent components.
2. The varnish according to claim 1, wherein The polymer compound is an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying all of the following conditions (1) to (4), (1) the number average molecular weight of the copolymer is 500 to 12,000, (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0 to 98% by mass. (3) the aromatic polyene is one or more selected from polyenes having a plurality of vinyl and / or vinylidene groups in the molecule and having a carbon number of 5 to 20, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 2 to 30 in terms of number average molecular weight, (4) It may contain one or more selected from olefin monomer units having 2 to 20 carbon atoms, and when aromatic vinyl compound monomer units and aromatic polyene monomer units are present, the total of the olefin monomer units is 100% by mass.
3. The varnish according to claim 2, wherein The content of the olefin-aromatic vinyl compound-aromatic polyene copolymer is in the range of 30% by mass or more and 69% by mass or less of the total mass of the varnish.
4. The varnish according to claim 1 or 2, wherein The multifunctional monomer includes divinylbenzene.
5. The varnish according to claim 4, wherein The content of divinylbenzene is 30% by mass or more in the total mass of the varnish.
6. The varnish according to claim 1 or 2, wherein: The monomer component further includes a monofunctional monomer.
7. The varnish according to claim 6, wherein The content of the monofunctional monomer is 40% by mass or less in the total mass of the varnish.
8. The varnish according to claim 6, wherein The monofunctional monomer comprises one or more selected from styrene, ethylvinylbenzene or acenaphthylene.
9. A cured product of the varnish according to claim 1 or 2.
10. The cured body according to claim 9, which is an electrical insulating material.
11. A CCL substrate, FCCL substrate, interlayer insulating material or cover layer, comprising the cured body according to claim 9.
12. A crosslinked resin matrix, which is a cured product of a varnish comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer and a multifunctional monomer component, wherein: The storage modulus of the cross-linked resin matrix at 280° C. is greater than 30 MPa.
13. The cross-linked resin matrix according to claim 12, wherein The storage modulus of the cross-linked resin matrix at 25° C. is greater than 80 MPa.
14. The crosslinked resin matrix according to claim 12 or 13, wherein the average value of the dielectric constant measured at 23°C and a frequency of 20 to 42 GHz using a balanced disk resonator is 2.5 or less and 2.0 or more, and the average value of the dielectric loss tangent is 0.0012 or less and 0.0003 or more.
15. The crosslinked resin matrix according to claim 12 or 13, comprising 99% by mass or more of carbon and hydrogen.
16. The cross-linked resin matrix according to claim 12 or 13, wherein The varnish contains substantially no solvent components.
17. The cross-linked resin matrix according to claim 12 or 13, wherein The varnish contains a solvent component.
18. The cross-linked resin matrix according to claim 12 or 13, wherein The olefin-aromatic vinyl compound-aromatic polyene copolymer satisfies all of the following conditions (1) to (4), (1) the number average molecular weight of the copolymer is 500 to 12,000, (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0 to 98% by mass. (3) the aromatic polyene is one or more selected from polyenes having a plurality of vinyl and / or vinylidene groups in the molecule and having a carbon number of 5 to 20, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 2 to 30 in terms of number average molecular weight, (4) It may contain one or more selected from olefin monomer units having 2 to 20 carbon atoms, and when aromatic vinyl compound monomer units and aromatic polyene monomer units are present, the total of the olefin monomer units is 100% by mass.
19. A method for producing a solidified body, the method comprising: A step of preparing a varnish comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer and a multifunctional monomer component; and A step of obtaining a cured product having a storage elastic modulus of 30 MPa or more at 280° C. by curing the varnish.
20. The manufacturing method according to claim 19, wherein: The storage modulus of the solidified body at 25° C. is greater than 80 MPa.
21. The manufacturing method according to claim 19 or 20, wherein: The olefin-aromatic vinyl compound-aromatic polyene copolymer satisfies all of the following conditions (1) to (4), (1) the number average molecular weight of the copolymer is 500 to 12,000, (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0 to 98% by mass. (3) the aromatic polyene is one or more selected from polyenes having a plurality of vinyl and / or vinylidene groups in the molecule and having a carbon number of 5 to 20, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 2 to 30 in terms of number average molecular weight, (4) It may contain one or more selected from olefin monomer units having 2 to 20 carbon atoms, and when aromatic vinyl compound monomer units and aromatic polyene monomer units are present, the total of the olefin monomer units is 100% by mass.
Citation Information
Patent Citations
Thermosetting resin composition having low dielectric constant
JP1994192392A
Resin composition having low dielectric loss tangent, cured product of the same, prepreg using the same composition, laminated plate and multilayered printed board
JP2003012710A
Resin composition of low dielectric dissipation factor and insulator and semiconductor device
JP2003105036A
Electronic part for high frequency using low dielectric loss tangent insulating material
JP2004087639A
Cross-copolymerized olefin / styrene / diene copolymer, process for the production of the same and uses thereof
JP2007217706A